Impact and blast resistance of uniform and graded sandwich panels with TPMS cellular structures - Novak, Nejc; Borovinšek, Matej; Al-Ketan, Oraib; Ren, Zoran; Vesenjak, Matej (Composite structures, 2022)
The impact and blast resistance of sandwich panels with uniform and functionally graded Triply Periodical Minimal Surface (TPMS) cellular cores were analysed in this study. The computational models were validated with available experimental compression tests of four different types of TPMS cellular structures (Diamond, Gyroid, IWP and Primitive). The IWP and Primitive structures showed comparable and overall lower critical velocities than Gyroid and Diamond structures, exhibiting a more significant strain-rate hardening effect. Two methods of cellular structure grading were applied: the sheet thickness grading (STG) and the cell size grading (CSG) throughout the structure. The performance of TPMS filled sandwich panels under blast loading was also computationally analysed and compared to the sandwich panels filled with strut-based cellular structures. Overall, the specific energy absorption of TPMS filled sandwich panels is up to 25% higher than in the sandwich panels filled with strut-based core with the same relative density. The introduction of graded porosity using thickness and cell size variation shows that it is possible to tailor the mechanical and deformation response of the TPMS structures and TPMS filled sandwich panels while maintaining comparable energy absorption capabilities.